The involvement of antioxidant, stress, and immune-related genes in the responsive mechanisms of common carp (Cyprinus carpio) to hypersalinity exposure - Ahmed, Hassan; Bakry, Karima A.; Abdeen, Ahmed; El bahgy, Halla E. K.; Abdo, Mohamed; Imbrea, Florin; Fericean, Liana; Elshemy, Mona A.; Ibrahim, Samah F.; Shukry, Mustafa; Baloza, Samar H.; Emeish, Walaa F. A. (Frontiers in Marine Science, 2023)
Salinity stress is one of the marked influencing factors on the ecophysiology of aquaculture and is considered an important reason for the retreat of the fish industry. The current study is an endeavor to elucidate the molecular mechanisms that underlie the response to salinity stress in common carp. Fish (Average weight 5 ± 2 g) were randomly distributed into two groups; the 1st is control exposed to tape water (0.2 ppt salinity) and the 2nd is hypersalinity-exposed group (10 ppt salinity) for five days. Serum biochemical indicators including total protein, albumin, globulins, A/G ratio, blood glucose, cortisone, Na+, K+, and Cl- levels were evaluated. Besides, Tumor necrosis factor-α, interleukin-1β, corticotropin-releasing hormone, and catalase enzyme mRNA expression levels were assessed in lymphoid and immunocompetent organs (liver and spleen) and osmoregulatory organs (kidney and gills) by using Real-time qPCR. Hypersalinity adversely affected the biochemical markers; total protein, albumin, and globulins decreased significantly however, blood glucose, serum cortisol, sodium markedly increased in fish exposed to hypersalinity compared with control. In addition, from the molecular point of view, all the evaluated genes upregulated in high expression rate in the liver compared with other studied organs after salinity challenge. On the contrary, hypersalinity modulated the expression of immune-related genes (Tumor necrosis factor-α and interleukin-1β) in the kidney and spleen and up-regulation of corticotropin-releasing hormone mRNA in all studied organs except gills. In conclusion, the obtained data clarified the molecular and biochemical mechanisms of salinity stress on the liver, kidney, spleen, and gills. Furthermore, it strongly suggests the implication of neural, endocrine, and immune systems in the responsive mechanisms to the salinity stress in carp.